Development of gluten‐free bread using low‐pressure homogenized rice flour supplemented with faba bean flour. Issue 2 (15th November 2021) - Boulemkahel, Souad; Garzon, Raquel; Benatallah, Leila; Rosell, Cristina M.
Abstract: Background and objectives: Low‐pressure homogenization (30 MPa‐3 passes) applied to long (LRF) and medium (MRF) rice grain flours was tested as physical method for improving gluten‐free breads (GFB) without additives. Rice flours were blended with faba bean flour (FBF) in the ratio 2:1 (w:w). Findings: Low‐pressure homogenization increased damaged starch content of rice flours and decreased the particle size distribution of blends, leading to higher volumes during batters' fermentation. Homogenization treatment improved the GFB texture profile, decreasing hardness and increasing cohesiveness and resilience. The crumb structure, particularly that of GFB from LRF:FBF blends, was greatly improved by the treatment, and better shape (lower width/height ratio) was obtained. No significant differences were found on the hardening rate of stored GFB, when using homogenized rice flours. Conclusions: In general, long rice homogenized flour revealed the greatest capacity to improve the GFB quality. Low‐pressure homogenization of long or medium rice flour can be an adequate physical treatment to improve breadmaking properties of rice flours. Significance and novelty: The study confirms the suitability of low‐pressure homogenized LRF and MRF blended with FBF as raw ingredient in GF breadmaking without additives.